2011
DOI: 10.2214/ajr.09.4108
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value for Malignancy of Suspicious Breast Masses of BI-RADS Categories 4 and 5 Using Ultrasound Elastography and MR Diffusion-Weighted Imaging

Abstract: Our results show that elasticity imaging provides relatively reliable predictions for malignancy, especially in BI-RADS category 4 masses, compared with MR DWI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 20 publications
0
25
0
Order By: Relevance
“…Previous studies (12,14,19,(22)(23)(24)(25)(26)35) have shown promising differences in ADCs between malignant and nonmalignant breast lesions and improved diagnostic accuracy through a multivariate combination of ADC and dynamic contrast-enhanced MR imaging features (18,20,36,38). Despite the potential advantages of DW imaging for breast imaging, substantial overlap exists between ADCs of malignant and nonmalignant lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies (12,14,19,(22)(23)(24)(25)(26)35) have shown promising differences in ADCs between malignant and nonmalignant breast lesions and improved diagnostic accuracy through a multivariate combination of ADC and dynamic contrast-enhanced MR imaging features (18,20,36,38). Despite the potential advantages of DW imaging for breast imaging, substantial overlap exists between ADCs of malignant and nonmalignant lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Because many diseases correlate with changes in the mechanical properties of tissues, this technique has been successfully applied in detecting and assessing various pathologies of thyroid gland, breast, lymph nodes, major salivary gland, prostate, kidney, and liver [1][2][3][11][12][13][14][15][16][17]. However, to our knowledge, no study has been reported previously in the medical literature using real time sonoelastography to assess gallbladder polyps.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we found in the majority of cases threelayered areas (blue, green, and red) on the elastogram, which were usually observed in the dependent portion of the gallbladder, and/or around the polyp. This appearance is an artifact of elastography due to liquid in the lumen of the gallbladder [12].…”
Section: Discussionmentioning
confidence: 99%
“…Solid mass in the breast is also a kind of benign breast tumor. Solid breast mass in patients carries a higher risk of breast cancer compared with no solid mass (OR = 1.384, 95%CI: 1.022-1.873), suggesting that clinicians who discover solid breast masses in patients should be alert to the risk of breast cancer (Satake et al, 2011).Organs from those whose occupations were staff and government had the highest detection rate of breast cancer, which may be due to a relatively high standard of living including normal intake of high fat and more high-calorie foods, leading to increased prevalence of breast cancer. Those occupations involve busy arduous tasks and mental stress, which result in a high rate of screening.…”
Section: Discussionmentioning
confidence: 99%